2013
DOI: 10.5861/ijrset.2012.170
|View full text |Cite
|
Sign up to set email alerts
|

Reading from an LCD monitor versus paper: Teenagers’ reading performance

Abstract: The purpose of the study was to examine differences in reading performance when an electronic test format with a scrolling text mode on a LCD monitor and a traditional paper test format were used to present reading tests to teenagers who belong to Generation Z. In this study, participants were 108 high school students who each read two different reading passages, one from paper and the other from an LCD monitor. The results show that teenagers' reading performance is affected by a presentation medium. Teenager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
(51 reference statements)
1
39
0
3
Order By: Relevance
“…In the screen condition, students were instructed to circle their responses using their computer mice, whereas students in the paper condition circled their responses using a pencil. Despite the conclusion of Wang et al (2008) that paper and computer-based testing are similar, it is possible that the different psychomotor demands of assessment in Kim and Kim (2013) were responsible for the substantially longer reading times in the paper than the screen condition.…”
Section: Reading Timementioning
confidence: 96%
See 1 more Smart Citation
“…In the screen condition, students were instructed to circle their responses using their computer mice, whereas students in the paper condition circled their responses using a pencil. Despite the conclusion of Wang et al (2008) that paper and computer-based testing are similar, it is possible that the different psychomotor demands of assessment in Kim and Kim (2013) were responsible for the substantially longer reading times in the paper than the screen condition.…”
Section: Reading Timementioning
confidence: 96%
“…There were limitations in the quality of the studies covered in this review. Across many of the studies, a common limitation is a lack of reliability statistics reported for measures (e.g., Ackerman & Goldsmith, 2011;Ackerman & Lauterman, 2012;Chen et al, 2014;Daniel & Woody, 2013;Green et al, 2010;Kim & Kim, 2013;Lauterman & Ackerman, 2014;Porion et al, 2016;Taylor, 2011). Reading comprehension is a multidimensional construct, which makes developing measures with good internal consistency challenging (Clinton, 2014;Kamalski, 2004).…”
Section: Limitationsmentioning
confidence: 99%
“…Research projects vary with respect to scope and method, and main findings concerning the effects of technological affordances on central aspects of reading are still to a considerable extent inconsistent. Some studies (Jeong, 2012;Kim & Kim, 2013;Mangen, Walgermo, & Brønnick, 2013;Stoop, Kreutzer, & Kircz, 2013a,b;Wästlund, 2007;Wästlund, Reinikka, Norlander, & Archer, 2005) find reading on screen to be inferior to reading on paper with respect to cognitive outcomes (e.g., reading comprehension). Other studies have found that there are no or only minor cognitive differences, and that the main differences are on a metacognitive level (Ackerman & Goldsmith, 2011) or pertain to subjective experience and evaluations rather than objective outcomes (Grzeschik, Kruppa, Marti, & Donner, 2011;Kretzschmar et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Other students and instructors have a full workload and planning feedback session for every student will inevitably become a scheduling nightmare. In order to decrease the workload, computer assisted writing (and reading) has been studied in an EFL context with promising results (Kazemzadeh & Fard Kashani, 2013;Kim & Kim, 2013). The advance of the instrumentation and the methodology used in the current study are the affordances they offer for distance learning education.…”
Section: Resultsmentioning
confidence: 97%